Geo-tourism Potential of Sand Bars and Oxbow lake at Buluh Cina, Kampar – Riau, Indonesia - Yuniarti Yuskar (Journal of Geoscience, Engineering, Environment, and Technology, 2016)
Buluh Cina Village is located at Siak Hulu District, Kampar Regency, Riau Province and its about 25 km from Pekanbaru City. This Village is designated as Tourism Village by The Government of Riau Province. This research aims to optimize the potential Geo-tourism by understanding the strengths and weaknesses aspect which is owned by Buluh China Village. So it can increase the number of tourists who visit Buluh Cina Village. The method used is the field survey and literature review. The village is surrounded by a tropical rain forest with an area of over 100 hectares and it divided by the Kampar Kanan River. Fluvial Meandering System of this river form the main channel (river), sandbars, natural levee, floodplain and oxbow lake. Geo-tourism potential that can be developed are sand bars and oxbow lake. Buluh China Village has had a tourist attraction, but there are still some weaknesses, such as floods in the rainy season and some support facilities are not optimal.